The additional value of real-time PCR in the quantitative detection of periodontal pathogens - Khalil Boutaga (journal of clinical periodontology, 2006)
Background and Aim: For the analysis of subgingival plaque, anaerobic bacterial culture has been the gold standard for many years. Currently, molecular microbial techniques have become available to identify and quantify target organisms with high specificity and sensitivity. The technique of real-time (RT-PCR) provides a new tool to detect oral pathogens both in oral and non-oral human infections. The aim of this study was to compare the RT-PCR and anaerobic culture for detection and quantification of six periodontal pathogens in periodontal health and disease. Material and Methods: Subgingival plaque samples from 259 adult patients with periodontitis and 111 healthy controls were analysed with quantitative anaerobic culture and quantitative RT-PCR for Actinobacillus actinomycetemcomitans, Porphyromonas gingivalis, Prevotella intermedia, Tannerella forsythia, Micromonas micros and Fusobacterium spp. Results: All species were more frequently isolated from patients than controls with both culture and RT-PCR. P. gingivalis, T. forsythia and M. micros appeared significant markers for disease with both techniques. P. intermedia was significantly associated with periodontitis by RT-PCR only (OR 9.7), whereas A. actinomycetemcomitans showed a significant relationship by culture only. The critical differences between culture and RT-PCR were culture-negative/PCR-positive samples which amounted to 7% for A. actinomycetemcomitans, 3% for P. gingivalis, 7% for T. forsythia, 20% for P. intermedia, 6% for M. micros, and 0.8% for Fusobacterium spp. in periodontitis patients and 12%, 3%, 2%, 35%, 14% and 0%, respectively, in the periodontally healthy group. Furthermore, periodontitis individuals had significantly higher amount of all of the test species in the subgingival plaque samples compared with healthy subjects. Conclusion: RT-PCR provides a new rapid diagnostic tool and opens the opportunity to detect small numbers of oral pathogens in clinical specimens, which are under the detection limit by culture technique.